Oral Candidiasis and Dry Mouth with SGLT2 Inhibitors in FAERS, 2013 Q1–2025 Q2: A Disproportionality Analysis - Rachmat Hidayat; Firman Hadi (Crown: Journal of Dentistry and Health Research, 2025)
Background: Oral adverse-event reporting with sodium-glucose cotransporter 2 (SGLT2) inhibitors remains poorly characterized. Objective: To evaluate disproportionate reporting of oral candidiasis, dry mouth, and periodontal disease with pure SGLT2 inhibitors in FAERS from 2013 Q1 through 2025 Q2. Methods: A retrospective case–non-case analysis used source-reported aggregates from 54 quarterly FAERS extracts. Latest-version handling, deletion-file exclusion, curated drug mapping, exact MedDRA Preferred Terms, reporting odds ratios (RORs) with 95% confidence intervals (CIs), and Benjamini–Hochberg-adjusted q values were applied. A signal required at least three co-reports, a lower CI bound greater than 1, and q < 0.05; role-scope and diabetes-indication comparator analyses assessed directional consistency. Results: Among 17,415,743 retained reports, 174,627 contained a mapped pure SGLT2 inhibitor. Primary-suspect analysis identified oral candidiasis (103 co-reports; ROR 1.71, 95% CI 1.41–2.07; q = 8.89 × 10−8) and dry mouth (578 co-reports; ROR 1.54, 95% CI 1.42–1.67; q = 1.99 × 10−24). Both estimates remained above 1 across broader role-scope and active-comparator analyses; periodontal disease was non-conclusive. Conclusion: Oral candidiasis and dry mouth showed hypothesis-generating disproportional reporting. The findings support targeted case review and external validation but do not estimate incidence, comparative risk, or causality.